Self-management and adherence in childhood-onset systemic lupus erythematosus: what are we missing?. (April 2019) - Harry, O; Crosby, L E; Smith, A W; Favier, L; Aljaberi, N; Ting, T V; Huggins, J L; Modi, A C
Objectives: The aims of this study are (1) to characterize factors influencing self-management behaviors and quality of life in adolescent and young adult (AYA) patients with childhood-onset systemic lupus erythematosus (cSLE) and (2) to identify barriers and facilitators of treatment adherence via focus groups. Methods: AYAs with cSLE ages 12–24 years and primary caregivers of the adolescents participated in this study. Recruitment occurred during pediatric rheumatology clinic visits at a Midwestern children's hospital or the hospital's cSLE active clinic registry. Information about disease severity was obtained from patient health records. Pain and fatigue questionnaires were administered. Descriptive statistics were used to analyze data. Results: Thirty-one AYA patients and caregivers participated in six focus groups. Ten major themes emerged from sessions; four were expressed both by the AYA and caregiver groups: knowledge deficits about cSLE, symptoms limiting daily function, specifically mood and cognition/learning, barriers and facilitators of adherence, and worry about the future. Themes unique to AYA participants included symptoms limiting daily functioning—pain/fatigue, self-care and management, impact on personal relationships, and health care provider communication/relationship. For caregiver groups unique themes included need for school advocacy, disruption of family schedule, and sense of normalcy for their adolescent. Conclusion: AYAs with cSLE face a lifelong disease characterized by pervasive pain, fatigue, organ damage, isolation—social and/or physical—and psycho-socioeducational challenges. This study confirmed that continued psychosocial support, health information education, adherence interventions, and personalized treatment plans are necessary to increase self-management and autonomy in AYAs with cSLE.